URGENSI KURIKULUM MUATAN LOKAL DALAM PENDIDIKAN - Nurdin Mansur (Jurnal Ilmiah Didaktika, 2012)
Human life is always in touch with the natural, social, as well as cultural environment in which the people live. Hence, it is necessary to apply local curriculum in primary schools to facilitate students to acquire learning resources surrounding. Curriculum development is supposed to be tailored to the needs of education in the region. In its implementation process, local curriculum requires appropriate strategies, take into account the purpose, materials, teachers, students, methods, media and evaluation. The matters related to these aspects will be discussed in the following article.